Larvicidal activity of cloves as an alternative to chemical control in mosquito vectors in the Amazonia under laboratory conditions (Research, Society and Development, 2023)
Mosquito-borne diseases continue to be the main causes of death in many tropical countries. Among the infectious diseases transmitted by mosquitoes, malaria and dengue fever remain a major public health concern. Chemical control is the most widely used method for controlling and preventing mosquito-borne diseases. However, there are reports in the literature about resistance in populations due to the continuous use of chemical insecticides. In this sense, products of plant origin, such as plant extracts, essential oils and plant derivatives, have emerged as a promising alternative. In this study, bioassays were carried out to evaluate the activity of the aqueous and methanolic extracts of cloves (Syzigium aromaticum) in laboratory conditions against Anopheles darlingi and Aedes aegypti larvae. The bioassays carried out with An. darlingi showed CL50 values of 6.41 µg/mL for the methanolic extract and CL50 values of 5.65 µg/mL for the aqueous extract. Considering the bioassays with Ae. aegypti larvae (aqueous extract), the CL50 value was 78.81 µg/mL and the methanolic extract showed a CL50 value of 131.10 µg/mL. The larvicidal activity of the methanolic extract (CL50 131.10 µg/mL) against Ae. aegypti larvae was much lower than that obtained with An. darlingi. Comparing the two mosquito species, An. darlingi was more susceptible to the aqueous and methanolic extracts. However, when comparing the activity of the extracts against An. darlingi, it was found that the aqueous and methanolic extracts were active. With regard to Ae. aegypti larvae, they were more susceptible to the aqueous extract.